Android-Based Introduction to Agricultural Crops and Pests - Aldi Susanto; Asti Rahayu Arjuni; Wal Ikram; Rismayani Rismayani (Universitas Bina Darma, 2022)
The number of farmers in Indonesia continues to increase during the pandemic. However, this increase was not accompanied by good literacy related to plants and pests. The main factor is the increasing amount of information that is not credible. This research was conducted to provide alternative solutions for farmers or the community, especially novice farmers in obtaining plant and pest information through an android application. This application was developed using the Kotlin programming language on Android Studio with the Waterfall Development Method. Based on the results of functional testing, the application can run well and pass all test scenarios using the Black Box method and can run on smartphones with Android 5.0 to 9.0 systems, without closing the possibility of a new Android version.